2011
DOI: 10.1007/s10661-011-2257-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pesticides used in agriculture on the development of precocious puberty

Abstract: The present study aims to evaluate the effects of pesticides on premature breast development. Forty-five girls (group 1) with premature breast development living in the Menderes region, where greenhouse cultivation is the main income, 16 girls (group 2) living in Izmir city with early puberty, and 33 girls (group 3) who had no signs of puberty were included in the study. Endosulphan 1, endosulphan 2, endosulphan sulphate, methoxychlor, vinclozolin, 4,4-dichlorodiphenyldichlorethylene (DDE), 4,-dichlorodiphenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 59 publications
(66 reference statements)
0
19
0
Order By: Relevance
“…Wolff et al (2008) do not find any change in timing of breast development in relation to serum DDE levels in girls in New York city (Table 5). Data on the timing of menarche (Table 6) after prepubertal exposure to DDE (DDT) are discrepant since it has been found to be early (Ouyang et al, 2005;Deng et al, 2012) or normal (Denham et al, 2005;Ozen et al, 2012). However, on account of the persistence of the insecticide in the body fluids, exposure earlier than in prepuberty cannot be excluded in these studies.…”
Section: Critical Windows Of Exposure To Endocrine Disrupters and Timmentioning
confidence: 99%
“…Wolff et al (2008) do not find any change in timing of breast development in relation to serum DDE levels in girls in New York city (Table 5). Data on the timing of menarche (Table 6) after prepubertal exposure to DDE (DDT) are discrepant since it has been found to be early (Ouyang et al, 2005;Deng et al, 2012) or normal (Denham et al, 2005;Ozen et al, 2012). However, on account of the persistence of the insecticide in the body fluids, exposure earlier than in prepuberty cannot be excluded in these studies.…”
Section: Critical Windows Of Exposure To Endocrine Disrupters and Timmentioning
confidence: 99%
“…They exert their effects by binding to hormone receptors, disturbing cell-signaling pathways, directly affecting the central neuro-endocrine system, inhibiting hormone synthesis and/or by their toxic effects on endocrine responsive organs. Continuous exposure to estrogens can pose severe health risks such as increased risk for breast cancer in adulthood, male and female infertility and precocious puberty (Krstevska-Konstantinova et al, 2001;Diamanti-Kandarakis et al, 2009;Ozen et al, 2012). Due to these health effects, there is growing attention on the presence of EDCs in our environment and our exposure to such chemicals.…”
mentioning
confidence: 99%
“…However, other researchers found no connection between pesticides and precocious puberty [17]. Certain data show that the increase in the pesticide level is accompanied by a reduction of the luteinizing [33] and steroid hormones [25].…”
Section: Discussionmentioning
confidence: 92%
“…For instance, some researchers [15,18] found a link between pesticides and precocious puberty, others [17] found no connection between the concentration of pesticides in the blood and adipose tissue and early puberty, while some [36] found that pesticides caused delayed puberty. These contradicting results may result from the use of different research objects (animals, humans) and different pesticides under consideration.…”
Section: Introductionmentioning
confidence: 99%